2005
DOI: 10.1259/dmfr/72474954
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of carotid artery calcification on the panoramic radiographs of patients with renal disease

Abstract: Carotid artery calcification was higher in haemodialysis patients and renal transplant recipients. These patients with such calcifications should be referred for further evaluation and treatment of carotid arteries, coronary arteries and vascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
5
21
2
Order By: Relevance
“…Activators of calcification are increased and inhibitors of calcification are reduced in patients with ESRD, resulting in metastatic vascular calcification, an important aetiology for vascular injury in these patients. 11,12,18 It has also been reported that the presence of these calcifications in ESRD patients causes increased stiffness in large, capacitive, elastic-type arteries like the aorta and common carotid artery. 19 Carotid artery calcification, especially when it occurs close to the carotid artery bifurcation, can result in important vascular obstruction, causing stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activators of calcification are increased and inhibitors of calcification are reduced in patients with ESRD, resulting in metastatic vascular calcification, an important aetiology for vascular injury in these patients. 11,12,18 It has also been reported that the presence of these calcifications in ESRD patients causes increased stiffness in large, capacitive, elastic-type arteries like the aorta and common carotid artery. 19 Carotid artery calcification, especially when it occurs close to the carotid artery bifurcation, can result in important vascular obstruction, causing stroke.…”
Section: Discussionmentioning
confidence: 99%
“…11 -13 Arterial calcifications are very common in patients with ESRD, and their presence has been found to be a strong predictor of cardiovascular morbidity and mortality. 11,12,14,15 In addition to atherosclerosis, there are also many other risk factors for cardiovascular disorders in these patients, 11 and so early detection of calcifications could provide life-saving information.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported a high prevalence of CAC in particular groups of patients, such as hemodialyzed patients (17.6%) (15), renal transplant recipients (15.7%) (15), patients with peritoneal dialysis (27.4%) (16), postmenopausal women (11%, 31%) (17,18), and patients with diabetes mellitus (24% not treated with insulin, 36% insulin-treated) (19), obstructive sleep apnea syndrome (22%), metabolic syndrome (22.4%) (20), and radiation treatment within the 10 years of having received irradiation (40%) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Stage 5 CKD is associated with increased calcification of the coronary [58][59][60][61], carotid [62][63][64][65][66][67], and peripheral [68] arteries. Coronary artery calcification can be apparent in patients with stage 1 or stage 2 CKD, and increases in severity as the disease progresses [68].…”
Section: Linking Ckd and Cvdmentioning
confidence: 99%